2007
DOI: 10.1614/ws-06-130.1
|View full text |Cite
|
Sign up to set email alerts
|

Response of Common Lambsquarters (Chenopodium album) to Glyphosate as Affected by Growth Stage

Abstract: Experiments were conducted to determine the efficacy of glyphosate on four common lambsquarters populations collected from Kansas, Nebraska, North Dakota, and Ohio. Glyphosate dose-response studies for common lambsquarters treated at 2.5-, 7.5-, and 15-cm heights showed that glyphosate at 1.1 kg ae ha−1caused more than 80% injury to 2.5-cm plants but less than 55% injury to 7.5- and 15-cm plants. All populations were susceptible to glyphosate at the 2.5-cm height. The glyphosate rate required to cause 50% inju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
37
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 33 publications
6
37
1
1
Order By: Relevance
“…Although common lambsquarters is considered a summer annual, emergence begins in the early spring and continues throughout the summer, and lateseason emergence is not unusual (Holm et al 1977;Schuster et al 2007). Thus, the ability of a few plants to escape control may lead to the production of thousands of seeds, continued infestations, and reduced crop yields in subsequent years.…”
Section: Competitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although common lambsquarters is considered a summer annual, emergence begins in the early spring and continues throughout the summer, and lateseason emergence is not unusual (Holm et al 1977;Schuster et al 2007). Thus, the ability of a few plants to escape control may lead to the production of thousands of seeds, continued infestations, and reduced crop yields in subsequent years.…”
Section: Competitionmentioning
confidence: 99%
“…Schuster et al (2007) have observed that the development of herbicide resistant common lambsquarters limits weed management options, and alternatives are generally less effective or more expensive. (Nandula et al 2005).…”
Section: Herbicide Resistance In Common Lambsquarters Herbicide Resimentioning
confidence: 99%
“…Ahmadi et al (1980) encontraron mayor efecto del glifosato en plantas de 5 y 10 cm de altura, que en las de 15 y 20 cm. Asimismo, Schuster et al (2007) determinaron que las plantas de Chenopodium album L. fueron más afectadas por el glifosato cuando su altura era de 2.5 cm, que cuando medían 7.5 ó 15 cm.…”
Section: Results and Discussion Experiments 1: Glyphosate Dosages And unclassified
“…Ahmadi et al (1980) found a greater effect of glyphosate in plants 5 and 10 cm high, than in 15 and 20 cm. Also, Schuster et al (2007) determined that plants of Chenopodium album L. were most affected by glyphosate when their height was 2.5 cm, than when measuring 7.5 or 15 cm.…”
Section: Results and Discussion Experiments 1: Glyphosate Dosages And mentioning
confidence: 99%
“…It is known that plants at the early growth stages are more susceptible to herbicides, due to greater absorption of the herbicide by young and rapidly growing plants than mature ones. Similarly, certain studies reported greater control with glyphosate in common fathen (Chenopodium album) when plants were relatively smaller (Schuster et al 2007). Besides the increasing leaf area, there are also important changes in the cuticle features.…”
Section: Lolium Perennementioning
confidence: 94%